Development of reflective co-sputtered nanostructured metallic films. (4th March 2021) - Prajwal, K.; Priyanka, G. L.; Hasan, Mohammed Adnan; Carmel Mary Esther, A.; Sridhara, N.; Rajendra, A.; Arya, S. B.; Dey, Arjun
ABSTRACT: DC magnetron co-sputtering technique is utilised to develop reflective Ag- and Al-based metal films co-sputtered with Ni deposited on quartz glass substrates. The sputtered films are characterised by field emission scanning electron microscopy (FESEM), atomic force microscopy (AFM) and X-ray diffraction (XRD) techniques to investigate microstructure, topology and phase analysis, respectively. Further, average thermo-optical properties such as solar reflectance, absorptance and IR emittance and electrical property such as sheet resistance of the deposited films are evaluated. The reflectance property as a function of wavelength is also investigated. Sputtered Ag and Al films show high (>93%) reflectance, however, co-sputtered Al + Ni and Ag + Ni offer comparatively lesser value, e.g. 45% and 73%, respectively. The significant lower reflectance of Al + Ni is possibly due to the presence of higher amount of Ni in the film and the formation of intermetallic compounds.